Effects of Alpha Tocopherol on Renal Glomeruli in Diabetic Mice - Saadia Rashid, Shadab Ahmed Butt, Samina Anjum (Journal of Rawalpindi Medical College, 2011)
Background: To evaluate the effects of alphatocopherol supplement on renal glomeruli of diabetic mice. Methods: In this randomized control trial,thirty adult male mice were randomly divided into three groups.Group A served as control group. Group B was made diabetic by the intraperitoneal injection of streptozotacin. Group C received injection streptozotocin and fed with alphatocopherol supplemented diet.After 12 weeks animals were sacrificed and their kidneys were removed for histomorphological study. Results: Diabetes caused significant changes in glomeruli of Experimental Group B as compared to Control Group A but these changes were prevented in alphatocopherol treated group. Majority(80%) of animals in Group B showed glomerulosclerosis of Grade 4 and 20% showed Grade 3 glomerulosclerosis. In Group C 70% animals showed no glomerulosclerosis where as 30% showed glomerulosclerosis of Grade 1. Conclusion: Alphatocopherol, as an antioxidant, has a protective role in improving streptozotocin induced glomerulosclerosis .